Correlates and Predictors of PTSD Symptoms Among Healthcare Workers During the COVID-19 Pandemic: Results of the egePan-VOICE Study - Steudte-Schmiedgen, Susann; Stieler, Lisa; Erim, Yesim; Morawa, Eva; Geiser, Franziska; Beschoner, Petra; Jerg-Bretzke, Lucia; Albus, Christian; Hiebel, Nina; Weidner, Kerstin (Frontiers in Psychiatry, 2021)
Background: The COVID-19 pandemic has led to ongoing challenges for health care systems across the world. Previous research has provided evidence for an increased prevalence of depression and anxiety as well as posttraumatic stress disorder (PTSD). In Germany, however, only scarce data on correlates and predictors for PTSD symptomatology in the context of the COVID-19 pandemic among health care workers (HCW) are available. Methods: This research is part of a large prospective web-based survey (egePan-VOICE study) among HCW in Germany. The current sample (N = 4724) consisted of physicians (n = 1575), nurses (n = 1277), medical technical assistants (MTA, n = 1662) and psychologists (n = 210). PTSD symptomatology was measured using the abbreviated version of the Impact of Event Scale (IES-6). In addition, sociodemographic, occupational, COVID-19-related, psychological (e.g., depressive symptoms, generalized anxiety) as well as work-related variables were assessed. Results: Our findings revealed significant higher PTSD symptoms with medium effect sizes among HCW reporting an increased self-report burden during the pandemic, increased fear of becoming infected or infecting relatives with the virus, sleep problems, feeling physically or mentally exhausted as well as increased levels of depressiveness and generalized anxiety. According to multiple linear regression analysis, the most relevant predictors for higher IES-6 scores were increased level of generalized anxiety and depressiveness, increased fear of infecting relatives as well as medical profession (MTA compared to physicians). Conclusion: Despite the cross-sectional design of our study, the here identified associations with PTSD symptomatology may provide a basis for future preventive interventions.